2012
DOI: 10.1007/s10877-012-9361-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac output and stroke volume as measured by non-invasive CO monitoring in infants with RSV bronchiolitis

Abstract: ∆CO was related to ΔSV and not Δ HR. The ∆CO and ΔSV were affected by fluid boluses. ΔRR correlated with ΔCO. Non-invasive CO monitoring can trend CO and SV in infants with bronchiolitis during hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Cardiovascular complications are described in up to 9% of hospitalized patients [ 26 ]. Significant cardiac output and stroke volume changes have been demonstrated in infants without heart disease who were hospitalized for bronchiolitis in relation with their respiratory distress [ 27 ]. Up to 50% of patients have a positive troponin or NT-proBNP assay at the time of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular complications are described in up to 9% of hospitalized patients [ 26 ]. Significant cardiac output and stroke volume changes have been demonstrated in infants without heart disease who were hospitalized for bronchiolitis in relation with their respiratory distress [ 27 ]. Up to 50% of patients have a positive troponin or NT-proBNP assay at the time of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of cardiac failure, for example, tachypnea, tachycardia, prolonged capillary refill time, and mottling of the skin, may be difficult to distinguish from the symptoms of RSV bronchiolitis itself. 8 Thus, Caplow et al 8 suggested that CO as a measure of cardiac function should be assessed in hospitalized infants with RSV infection. The aim of this study was to investigate a predefined set of echocardiographic functional parameters, including right and left ventricular output, in relation to s-troponin, the need for supplementary oxygen or noninvasive respiratory support, and capillary refill time in children with RSV infection admitted to a regular pediatric ward.…”
Section: Introductionmentioning
confidence: 99%
“…This device estimates CO, CI, stroke volume (SV), SI, and a variety of other cardiac parameters using a complex mathematical algorithm (electrical velocimetry relates the maximum rate of change of impedance to peak aortic blood acceleration during the cardiac cycle) with the simple application of four EKG electrodes . The accuracy of this monitor has been validated and compared with other measures of CO such as the Fick equation , thermodilution , and echocardiography in diverse pediatric populations including patients with congenital heart disease and critical illness , neonates , and obese adolescents . One study of patients who had recovered from critical illness demonstrated a bias toward underestimation of CI and another found it to be useful in patients who had undergone cardiac surgery .…”
Section: Discussionmentioning
confidence: 99%